Proteomic and peptidomic UHPLC-ESI MS/MS analysis of cocoa beans fermented using the Styrofoam-box method. (30th June 2020) - Scollo, Emanuele; Neville, David C.A.; Oruna-Concha, M. Jose; Trotin, Martine; Umaharan, Pathmanathan; Sukha, Darin; Kalloo, Rena; Cramer, Rainer
Highlights: Over 1000 peptides have been detected from cocoa beans in all fermentation stages. The highest number of peptides were identified after 2 and 4 days of fermentation. The vast majority of the detected peptides originated from vicilin and a 21 kDa albumin. Potential markers to assess the degree of fermentation of cocoa beans are proposed. PCA of the peptidomic and proteomic data allows the separation of fermentation time points. Abstract: This work characterises the peptide and protein profiles of Theobroma cacao beans of the genotype IMC 67 at different fermentation stages, using the Styrofoam-box fermentation method and employing UHPLC-ESI MS/MS for the analysis of peptides and proteins extracted from the beans. A total of 1058 endogenous peptides were identified and quantified over four fermentation time points. The majority of these peptides were formed after 2 and 4 days of fermentation, and originated predominantly from the proteolysis of two storage proteins – vicilin and a 21 kDa albumin. The changes in the peptide profile over fermentation were subsequently evaluated, and potential markers for assessing the degree of fermentation were identified. In particular, changes of the relative abundance of the major cocoa proteins detected can be proposed as potential markers for the fermentation stage. Furthermore, PCA of both the peptidomic and proteomic data has allowed differentiation of beans at different fermentation stages.